2011
DOI: 10.3171/2011.5.spine10778
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–based morphometric analysis of the human occipital condyle for occipital condyle–cervical fusion

Abstract: Object Occipital condyle screws serve as an alternative fixation point in occipital-cervical fusion. Their placement requires a thorough understanding of the anatomy of the occipital condyles and associated structures. This study is a CT-based morphometric analysis of occipital condyles as related to occipital condyle–cervical fusion. Methods A total of 170 patients were examined with CT scans of the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 11 publications
2
33
4
Order By: Relevance
“…Asymmetry in OC dimensions has been reported by Agnihotriet al (2014), [20] and Bazyatet al (2014), [18] in which they stated that the right OC parameters had mean values significantly greater than the left; however, Lang (1995), [33] Cicekcibasiet al (2004), [8] and Tale et al's (2016), [34] reported no significant bilateral differences in the condyle parameters. The hypothesis of difference in data acquisition (radiologic, osteometric and photogrammetric) report by Lang and Hornung (1993), [23] inconsistencies in collection methods (Bozbugaet al, 1999), [15] and genetic endowment (Le et al, 2011;Yu et al, 2015); [13,14] as well as racial/ethnic differences (Lang and Hornung, 1993;Lang, 1995;Bozbugaet al, 1999;Cicekcibasiet al, 2004), [8,15,23] are undoubtedly factors which could impact on the range differences in the value obtained in morphometric studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asymmetry in OC dimensions has been reported by Agnihotriet al (2014), [20] and Bazyatet al (2014), [18] in which they stated that the right OC parameters had mean values significantly greater than the left; however, Lang (1995), [33] Cicekcibasiet al (2004), [8] and Tale et al's (2016), [34] reported no significant bilateral differences in the condyle parameters. The hypothesis of difference in data acquisition (radiologic, osteometric and photogrammetric) report by Lang and Hornung (1993), [23] inconsistencies in collection methods (Bozbugaet al, 1999), [15] and genetic endowment (Le et al, 2011;Yu et al, 2015); [13,14] as well as racial/ethnic differences (Lang and Hornung, 1993;Lang, 1995;Bozbugaet al, 1999;Cicekcibasiet al, 2004), [8,15,23] are undoubtedly factors which could impact on the range differences in the value obtained in morphometric studies.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] The occipital condyle (OC) and basilar process (BP) are structures located at the skull base which forms part of the floor of the cranial cavity which by location, differentiates the brain from facial structures and suprahyoid neck (Rautet al, 2012). [9] Name & Address of Corresponding Author Aigbogun (Jr) [8,13,14] with higher values reported for the Asians (Bozbugaet al, 1999; Yu et al, 2015; Salujaet al, 2016), [14][15][16] and lower values for the Caucasians and Australians (Wen et al 1997;Bazyatet al, 2014), [17,18] while for Africans the values fall between values of Asians and Caucasians (Salihet al, 2014; Agnihotriet al, 2014). [19,20] Only a few studies have reported morphometric values for the basilar process (clivus), with dimensions ranging from 24mm to 27mm (Oliviera, 1975; Wescott and Moore-Jansen, 2001), [21,22] and higher values for whites when compared to blacks (Wescott and Moore-Jansen, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially described in 2008 by La Marca et al, 15 then further investigated by Kosnik-Infinger et al 13 and Uribe and colleagues 16,17,25 via radiological and cadaveric analysis, the technique has since been shown to be a viable method to fuse the occiput and cervical spine. Specifically, it has been used in a pediatric setting of craniocervical instability from tumor surgery, craniovertebral anomalies, and prior suboccipital decompression.…”
Section: Discussionmentioning
confidence: 99%
“…However, screw and rod fixation methods were less beneficial to tumor patients. Furthermore, a number of studies have recently suggested that OC screw fixation can be a viable and safe alternative for patients who are not eligible for occipital steel plate fixation (6,7,(15)(16)(17)(18). Recent advent and improvements in surgical imaging and reconstruction have made occipitocervical arthrodesis by screw fixation a valuable tool in the surgical armamentarium of medical practitioners around the world.…”
Section: Abbreviations: Male (M) Female (F) Left (L) Right (R)mentioning
confidence: 99%